Leasing As Another Option For Financing - A Case Study On SAP And Flextronics Technology (Malaysia) Sdn Bhd - Ramasamy, Premalatha (2006)
The primary focus of this dissertation is to explore how leasing should be harnessed to facilitate the funding of organizational activities and resources. Research revealed that the literacy level concerning leasing benefits is rather low. Firms are still very precautious and skeptical about the returns they could derive out of leasing and the models used to evaluate the benefits (after tax) of leasing as a strategic financial tool.